Learning Cycle 5e Model In Student Work Sheet Material Rank - Sari, Amalia Vidya (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
Teaching materials that are too monotonous and have no color in the LKPD which is currently used by many students at school make students less interested in seeing and even reading them. The purpose of this study was to develop Mathematics LKPD using the 5E Learning Cycle Model on rank material. This research is a development research (RnD) using a 4-D model, namely the define stage, the design stage, the develop stage and the disseminate stage. However, it was modified into 3-D because the medium for its application did not reach its deployment. The research instruments were the RPP due diligence questionnaire and the LKPD due diligence questionnaire. Based on the results of expert validation, from the results of the final assessment on RPP validation by the three experts with an average of 4.4 with a percentage of 88.5%, namely the very feasible category. The results of the final assessment on LKPD validation by the three experts with an average score of 4.3 with a percentage of 87.3%, namely the category Very feasible. Based on these data it can be concluded that the development of Student Worksheets Based on the 5E Learning Cycle Model on Rank Material is very feasible to use.Keywords: Student Worksheets, Learning Cycle 5E Model, Rank Material.